Tradition of Using Susungan to Carry Corpses to Cemetery on The Custom of Death in Nagari Bukit Tantang, Bukit Sundi District Solok Regency - Amalia Lubis, Riski; Endrizal (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research is entitled "The Tradition of Using Susungan for Maanta Mayit Ka Pabururan in Death Customs in Nagari Bukit Tandang, Bukit Sundi District, Solok Regency". The purpose of this study is to describe the process of implementing susungan in the death custom in Nagari Bukit Tandang and reveal the meaning contained in the use of susungan to maanta moringa ka pabururan. The theory used in this study is the Interpretive Theory of Symbols from Clifford Geertz. The methods used in this study were carried out by observation, interview and documentation methods. The data analysis technique in this study uses steps including data reduction, data presentation and conclusion drawn. The results of this study show that susungan is a traditional coffin made of bamboo and covered with a long cloth. The main materials for making susungan are batuang (bamboo), tagut (small bamboo), palapah anau (pepelah palm), wood and rope. The amount of money used to carry funeral remains varies depending on the social status of the body in the community. The meaning contained in the tradition of using susungan for maanta mayit ka pabururan in the death custom in Nagari Bukit Tandang in general is the meaning of togetherness and mutual cooperation with the existence of this susungan the community can show high concern and solidarity in the Nagari Bukit Tandang community, in addition to the meaning of mutual cooperation there is also a meaning that there is social stratification in the Nagari Tandang community, This can be seen from the difference in the shape of the body used to transport the body to the cemetery depending on the social status of the body in the community.